Kształtowanie się mnożnika cena/zysk w cyklu życia przedsiębiorstwa - Słoński, Tomasz (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2007)
Comparable valuation techniques require careful examination of all underlying assumptions (i.e. cost of capital, dividend policy, return on equity). The problem becomes more complicated when cyclical firm is valued. In this case, additional informations about the stage of business cycle and firm's future prospects must be taken into consideration. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1183, s. 458-466